Programmed Cell Death 1 and Hepatocellular Carcinoma: An Epochal Story - DEMİRTAŞ, COŞKUN ÖZER; GÜNDÜZ, FEYZA (SPRINGER, 2022)
In recent years, immune-based therapies have emerged as novel pillars for hepatocellular carcinoma (HCC). The rationale of immune-checkpoint inhibitors (ICIs) trial in HCC originated from the fact that the tumor cells and the infiltrating stromal and immune cells promote an immunosuppressive tumor microenvironment, including the up-regulation of immune checkpoint molecules on their surface. Antibody-based blockage targeting inhibitory checkpoint molecules on cytotoxic T cells, including programmed cell death-1 (PD-1) or its counterpart on antigen-presenting cells has shown strong anti-tumor activity in a subset of HCC patients. Single nucleotide polymorphisms (SNP) of PD-1 gene may affect the PD-1 expression or function, which eventually can cause dysfunctionality of immune balance. Based on the inhibitory role of PD-1 in anti-tumor responses, it has been investigated in several studies as a candidate to test for genetic susceptibility of individuals to HCC. The present paper highlights the knowledge on cross-talks for liver immunology and HCC course, recent studies investigating the role of functional SNPs of PD-1 gene in Turkish HCC population, and the data on already investigated PD-1 inhibitor molecules in clinical trials.
Keywords: Immune-checkpoint inhibitor; Programmed cell death-1; Hepatocellular carcinoma; Single nucleotide polymorphism; PLUS BEVACIZUMAB; PATIENTS PTS; PHASE-III; EXPRESSION; ASSOCIATION; SORAFENIB; GENE; SUSCEPTIBILITY; POLYMORPHISM; MULTICENTER